Leverage certificates’ design within the portfolio management - Harčariková, Monika; Bobriková, Martina (Univerzita Pardubice, 2019)
The paper examines an analysis of leverage certificates (namely turbo certificates), where their value is derived from an underlying asset and barrier options. Turbo certificates are riskier financial instruments that provide much more gains or losses due to leverage effect. There are introduced long turbo (for increasing markets) and short turbo certificates (for markets drop). The replicating portfolios profit is identical to a profit from the combination of an underlying asset and barrier options as it is proved in the paper. Based on theoretical approach, replicating portfolios for long and short turbo certificates on Google and Facebook companies are engineered with various parameters and calculated the certificates prices and financial leverages. Their profitability is disproportionately high what it is proved due to low capital investment and the leverage. The main objective is to demonstrate the nature of the given certificates creation using barrier options in an analytical form. The use of proposed turbo certificates can be one of the alternatives for creating a diversified portfolio for investors to reduce risk in case of unforeseen stock price developments. The results of our analysis help the increasing of the intellectualization of all potential investors. After that they will be able to make the best investment decisions in future according to the expectations of UA’s price development.
Keywords: long turbo certificate; short turbo certificate; barrier options; financial leverage; profitability; G11; G13